PERBEDAAN TINGKAT PENGETAHUAN IBU TENTANG GAKI DAN STATUS GIZI ANAK USIA 24- 59 BULAN DI DESA BERINGKIT DAN DESA BATANNYUH - Ni luh Dewi Sundari; I Made Purnadhibrata; I Gusti Putu Sudita Puryana (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2020)
The age of toddlers is a very important age for the growth and development of children. Mother's knowledge of the provision and selection of food ingredients is needed to provide good nutrition to children. One of the efforts made to prevent disorders due to lack of iodine is the iodized salt program. The purpose of the study was to determine the differences in the level of mothers knowledge about IDD and nutritional status of children aged 24-59 months in Beringkit Belayu Village and Batannyuh Village. This type of research is observational with a cross-sectional design. The sample obtained was 63 samples. Test the statistics using the Independent sample t-test. In the research subjects in Beringkit Belayu Village with 30 people (88.2%) good knowledge of 34 people, and 5 people (17.2%) with good knowledge in Batannyuh Village of 29 people. In the research subjects in Beringkit Belayu Village 32 samples (94.1%) with normal nutritional status, 2 samples (5.9%) with high nutritional status. In Batannyuh village there were 23 children (79.3%) with normal nutritional status, 5 children (17.2%) with short nutritional status and 1 child (3.4%) with very short nutritional status. Statistical test results (p = 0,000) means that there is a difference in the level of mothers knowledge about IDD and nutritional status of children aged 24-59 months in Beringkit Belayu Village and Batannyuh Village, Marga District, Tabanan Regency. Keywords: Level of knowledge about IDD, children's nutritional status and iodized salt program